Seize Of Life And Human Rights And Discrimination Against Asians And Black People In The United States From A Criminal Law Perspective International - Indira Putri Elharisa Kirana; Hilda Husnul Khotimah; Muhammad Dhanu Fitransyah; Yesariza Nabila; Herli Antoni (Universitas Djuanda, 2024)
The author’s aim in taking the title of this research is to provide a general explanation regarding racism which include an international criminal law. However, implementation for certain racial groups has not been fully implemented. We can see this from the existence of racism carried out on citizens in the united states toward the African-American race and the Asian race. Justice for those with dark skin and Asians has not been realized until now, many of them have experienced injustice through racially motivated attacks, resulting in the death of individuals and groups. The application of legal rules and legal protection from the united nations for Asians and black people has not yet been fully paid attention to in the united states, this is proven by the case of George Floyd’s death.